Mapping healthy aisles in Makassar city, Indonesia: implications for community empowerment - Sukri Palutturi; Lalu Muhammad Saleh; Muhammad Rachmat; Jalaluddin Abdul Malek (Elsevier, 2021)
Objective: The purpose of this paper was to map healthy aisles in Makassar City and how its implication is for community empowerment. Method: This research was a descriptive survey. One hundred and sixty aisles in Rappocini and Ujung Tanah Sub-Districts, Makassar were surveyed. Results: The development of healthy aisles is under maintenance of Puskesmas (Public Health Center) consisting of 20 aisles of 117 aisles in Puskesmas Kassi-Kassi and 3 aisles of 43 aisles in Puskesmas Pattingalloang. Ten healthy aisles indicators were established: aisles's cleanliness, beauty, drainage, garbage transportation, utilization, Siskamling (neighborhood security system), Non-Smoking Area (Kawasan Tanpa Rokok = KTR), active Posyandu (Integrated Health Post), the presence of educational media and the existence of working groups (Pokja). Conclusions: Based on 10 healthy aisles indicators, aspects of beauty, educational media, and aisles work group activity need to be strengthened, while others need to be maintained and even improved.